ANALISIS PRESTASI BELAJAR SISWA DAN KETERLAKSANAAN PROCESS ORIENTED GUIDED INQUIRY LEARNING DITINJAU DARI JENIS KELAMIN - Mega Lestari Putri; Hasan Subekti (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study aimed to find the effect of the POGIL learning method and students’ gender on their learning performance. The type of research used was one group pretest-posttest design and quantitative descriptive. Data collection techniques used were observation and test methods. The data have been collected through observation and test result. The instruments used in this research were: (1) observation sheets of POGIL learning method application, (2) pretest and posttest of students’ cognitive abilities (3) self-assessment sheets of students’ affective abilities, and (4) science process skill observation sheets of students’ psychomotor abilities. The participants in this study were 20 students in the city of Surabaya with 8 male students and 12 female students. This research showed the implementation of the POGIL learning method significantly affected the students’ affective, cognitive, and psychomotor performance. Majority of the research subjects achieved a very good grades on their affective test, meanwhile the minority of students’ psychomotor abilities achieved an average score. Genders also influence their learning performance, with female students performing better than male. In conclusion, the implementation of the POGIL learning method and the students’ gender are two elements that simultaneously affect their learning performance.